2016
DOI: 10.1186/s12951-016-0206-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduced graphene oxide: nanotoxicological profile in rats

Abstract: BackgroundWe have previously demonstrated that reduced graphene oxide (rGO) administered intravenously in rats was detected inside the hippocampus after downregulation of the tight and adherens junction proteins of the blood–brain barrier. While down-regulators of junctional proteins could be useful tools for drug delivery through the paracellular pathway, concerns over toxicity must be investigated before clinical application. Herein, our purpose was to trace whether the rGO inside the hippocampus triggered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 40 publications
1
50
2
Order By: Relevance
“…The large size of rGO hinders drug delivery in the bloodstream. Mendonça et al 28 reported that small-size graphene oxide is easily phagocytosed and more applicable for drug loading. In this study, we used rGo-Ag nanocomposite.…”
Section: Discussionmentioning
confidence: 99%
“…The large size of rGO hinders drug delivery in the bloodstream. Mendonça et al 28 reported that small-size graphene oxide is easily phagocytosed and more applicable for drug loading. In this study, we used rGo-Ag nanocomposite.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro concentration of rGO-PEG (100 µg/ml) was selected as a function of the concentration already used for in vivo experiments (7 mg/kg) [10,11]. For the calculation, we considered a 200 g rat with blood volume average of 14 ml [15].…”
Section: Toxicity Measurementsmentioning
confidence: 99%
“…We have previously demonstrated that water-suspended rGO injected in rats through the tail vein (i.v.) induces a transient disruption of the paracellular tightness of the blood-brain barrier (BBB) in the hippocampus [10], with a relatively low toxicity for the vital organs [11]. The BBB is a dynamic interface that separates the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 peripheral circulating blood and the CNS microenvironment.…”
mentioning
confidence: 99%
“…If the graphene oxide sizes are too large, drug delivery in the blood stream would be affected. Whereas if graphene oxide sizes are too small, drug loading would be affected, and particle phagocytosis would readily occur [23]. Thus, in the present study, we concluded that the size of graphene oxide should be approximately 300 nm (achieved through gradient centrifugation) to ensure its drug loading and to avoid phagocytosis by phagocytic cells in vivo.…”
Section: Discussionmentioning
confidence: 60%